Corporations are people too : (and they should act like it) - Greenfield, Kent (Yale University Press, 2018)
"Are corporations people? The U.S. Supreme Court launched a heated debate when it ruled in Citizens United that corporations can claim the same free speech rights as humans. Should corporations be able to claim rights of free speech, religious conscience, and due process? Kent Greenfield provides an answer: Sometimes. With an analysis sure to challenge the assumptions of both progressives and conservatives, Greenfield explores corporations' claims to constitutional rights and the foundational conflicts about their obligations in society. He argues that a blanket opposition to corporate personhood is misguided, since it is consistent with both the purpose of corporations and the Constitution itself that corporations can claim rights at least some of the time. The problem with Citizens United is not that corporations have a right to speak, but for whom they speak. The solution is not to end corporate personhood but to require corporations to act more like citizens"--